Oral health of children and adolescents with or without attention deficit hyperactivity disorder (ADHD) living in residential care in rural Rhineland-Palatinate, Germany - Vicky Ehlers; Angelika Callaway; Sophia Wantzen; Michael Patyna; James Deschner; Birgül Azrak (BMC, 2019)
Abstract Background Attention deficit hyperactivity disorder (ADHD) is defined as childhood neurobehavioural disorder. Due to short attention span, oral hygiene and dental treatment of such individuals can be challenging. Aim of this study was to evaluate the oral health of children and adolescents with and without ADHD living in residential care in rural Rhineland-Palatinate, Germany. Methods Included in the study were 79 participants (male/female:58/21, age 9-15 years) living in residential care: 34 participants with ADHD and 45 participants without ADHD (control). Oral examination included the following parameters decayed, missing, filled teeth in the primary dentition (dmft), decayed, missing, filled surfaces/teeth in the secondary dentition (DMFS/DMFT), approximal plaque index (API), bruxism and orthodontic treatment. Additionally, oral hygiene, last dental visit and treatment performed, and dietary habits were assessed by questionnaire. Results There were no significant differences in dmft, API, bruxism and oral hygiene habits between groups. However, participants with ADHD tended to have higher DMFS/DMFT values than the control group. Ongoing orthodontic treatment was found more often in the control group. The ADHD group tended to consume acidic/sugary beverages and sweet snacks more often than the controls. Different treatments (control visit/prophylaxis, dental therapy, orthodontic treatment) were performed at the last dental visit in the two groups. Conclusions Within the limitations of this study, oral health was similar in children and adolescents with or without ADHD from the same residential care setting. Parents/guardians need instructions for better supervision of oral hygiene and dietary habits to improve the poor oral health of children with or without ADHD.